Antifogging and Antireflective Coatings by Spin-LbL Assembly of SiO2 and ZrO2 Nanoparticles - Yang, Fusheng; Wang, Peng; Yang, Xiaoli; Cai, Zaisheng (Nanoscience & Nanotechnology-Asia, 2019)
Background: Fogging is a common phenomenon and often causes trouble to people in daily life. Antifogging (AF) and Antireflective (AR) coatings can be effectively used to provide resistance to fogging and maintain the optical clarity in day-to-day life. For this reason, they are useful for maintaining optical clarity in optical instrument and display devices. Methods: Antifogging and antireflective coatings were fabricated using a Spin-LbL assembly process, and this process is driven by electrostatic interactions between the positively charged ZrO2 NPs and negatively charged SiO2 NPs. Results: The textured surfaces and void fraction can significantly enhance the wettability of surfaces with water. And this may result in enhanced AF properties. In the Water contact angles (WCA) test, the ZrO2/SiO2 and SiO2/ZrO2 coatings were all superhydrophilic (almost 0°, less than 0.04 s). In the boiling test and low temperature AF test, the ZrO2/SiO2 and SiO2/ZrO2 samples showed excellent AF properties. Conclusion: Antifogging and antireflective coatings were fabricated via Spin-LbL assembly of the positively charged ZrO2 NPs and negatively charged SiO2 NPs followed by calcination. The resultant coatings showed excellent AF properties due to the superhydrophilicity of the coating, exhibited excellent AR properties due to the low refractive index coating and an appropriate coating thickness, and showed excellent superhydrophilic properties due to a nano-roughness structure.
Keywords: optical clarity